A four-year study of cirrhosis at Groote Schuur hospital - Solombela, Archie Cornelius Siyolo (Department of Medicine, 2017)
INTRODUCTION: Groote Schuur Hospital (GSH) is a large academic hospital Cape Town. It serves a population of about 2 million, comprising three population groups, black people of African origin, coloured, who are people of Asian or mixed origin, and white - of European descent. The hospital serves as a secondary referral centre for the surrounding regions, as a tertiary referral centre for the Western Cape province and much of the Eastern Cape province, and as a quaternary super-specialist centre for certain services, including liver and cardiac transplantation, for much of South Africa. A significant number of patients with cirrhosis present for the first time at Groote Schuur Hospital with decompensation and a diagnosis of cirrhosis is made on the basis of association of signs of liver failure, portal hypertension, radiological features consistent with cirrhosis with or without a proven cause of cirrhosis (personal observation). A study in Italy and another study done in Birmingham showed that a proportion of 63% and 65% respectively of patients have decompensated cirrhosis when first seen and in the English study the figure was unchanged in 18 years (Saunders et al 1981, D'Amico et al 1986). Most patients with cirrhosis remain compensated for many years and have a relatively long-life expectancy. Clinical decompensation, which is evidenced by the development of one or more complications, has a poor prognosis. The high rate of repeated consultations in patients with cirrhosis confirmed the high morbidity associated with this condition (Dufour et al 1993). In the United States between 1973 and 1983, cirrhosis mortality declined by one third to 10.2/100 000 deaths and the decline continued through to 1987 when the death rate reduced to 9.2/100 000 deaths. Furthermore, an increase in morbidity was observed with this decreasing mortality rate (Noble et al 1993). AIM OF THE STUDY: Accordingly, this study was intended to delineate the demographic and clinical profile of patients with cirrhosis admitted to our hospital, to assess the relative importance of the various underlying causes of cirrhosis, to assess the frequency of complications of cirrhosis and describe their presentation and management, to assess the outcome of treatment and to estimate its cost.